Frequency of Thrombocytopenia and Associated Mortality in Neonates with Neonatal Sepsis - Imran Ahmad, Ghulam Shabir Laghari, Muhammad Amir, Hafiz Abdul Quddus, Muhammad Sajjad Sabir, Masood Murad Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the frequency of thrombocytopenia and associated mortality in neonates with neonatal sepsis. Methodology: This descriptive study was designed to identify the frequency of thrombocytopenia in neonates and conducted at Nazir Hussain Medical Complex KKF Hospital Hyderabad from 1st September 2022 to 28th February 2023 after ethical clearance through the institutional review committee. This study enrolled 190 neonates which were admitted in NICU with the diagnosis of neonatal sepsis. All those neonates under 28 days of age and having a positive blood culture reports were included. A 3cc whole blood was drawn from each neonate by a nursing staff in a single pick and blood test including haematological markers (haemoglobin, platelet count) and infection markers (white blood cells, neutrophil%, Lymphocyte%, C-reactive proteins and Erythrocyte sedimentation rate) were analyzed. Results: There were 60% male neonates while rest 40% were females. About 44.78% had a weight between 2.5-3.5kg. The mean platelet count was 182.95±156 x109/L whereas lymphocytes% mean value was 41.81±11.0% with a very high ESR reported as 21.08±14.2mm/hour. The frequency of thrombocytopenia was observed in 129(67.89%) neonates wherein it was observed as severe in 35(18.4%) neonates and the frequency of mortality was observed as fourfold increased in the cases of thrombocytopenia. Practical Implication: Factors like age, low birth weight, platelet count and severity of thrombocytopenia are related with outcomes of neonatal sepsis among neonates. Conclusion: There is a high frequency of thrombocytopenia within the cases of neonatal sepsis. The mortality is higher in cases with severe thrombocytopenia. Keywords: Frequency, Thrombocytopenia, Associated mortality, neonate, neonatal sepsis